Evaluating the impact of the ASSETS 2024 program on skill enhancement in tahfiz students - Affendy Lee, Noor Azli; Wan Pazilah, Wan Muhammad Nurhanis (Universiti Teknologi MARA, Kedah, 2024)
This study explores the effectiveness of the Aiding in Sustainable Skills Empowerment & Transfer (ASSETS) 2024 program in enhancing various skills among participants, including English proficiency, mathematical abilities, and practical skills such as frisbee playing, hair cutting, ice cream making, and body massage. The primary objective is to evaluate the impact of the 3-day knowledge transfer program on these skills and identify areas of improvement. A survey was conducted among 21 tahfiz participants from a maahad in Sungai Petani, Kedah, assessing their proficiency and interest in the targeted skills before and after the program. The survey included questions on English and mathematical proficiency, specific interests in mathematics and practical skills like frisbee playing, hair cutting, ice cream making, and body massage. The results revealed a significant improvement in participants' skills across all areas. Many participants reported enhanced English proficiency. Similarly, mathematical abilities showed notable advancements, with increased interest and proficiency. Practical skills also saw improvement, with participants expressing increased confidence and competence in frisbee playing, hair cutting, ice cream making, and body massage. In conclusion, the ASSETS 2024 program effectively enhanced the participants' skills, meeting its primary objectives. The study highlights the importance of structured programs in skill development and recommends the continuation and expansion of such initiatives to further benefit participants. Future research should focus on long-term impacts and explore additional skills that could be integrated into the program.